Harper's illustrated biochemistry - Murray, Robert K; Bender, David A.; Botham, Kathleen M.; Kennelly, Peter J.; Rodwell, Victor W. (New York, McGraw Hill, 2009)
The principles of biochemistry and molecular biology as they relate to medicine. The Twenty-Eighth edition features a conversion to full-color art, the addition of case studies to every chapter, a larger trim size, and new pedagogy.
Includes bibliographical references.; Appendix I-II, 647-650p.; Index 651-693p.
Keywords: Biochemistry